PENGARUH ONLINE CUSTOMER REVIEW DAN ONLINE CUSTOMER RATING TERHADAP KEPUTUSAN PEMBELIAN ONLINE PADA PRODUK DI MARKETPLACE SHOPEE OLEH PELANGGAN DI KOTA BANJARMASIN - Gilang Noor Pratama; Rizki Muslim Hidayat; Noor Hidayati; M. Hasanur Arifin (Smart Business Journal (SBJ), 2025)
This study aims to identify and examine the partial and simultaneous effects of Online Customer Review and Online Customer Rating variables on Online Purchase Decisions of products on the Shopee marketplace by customers in Banjarmasin City. This study uses a quantitative approach, the research location is in Banjarmasin. A sample of 100 respondents who have purchased products online in the Shopee marketplace were selected randomly through accidental sampling techniques. Data analysis using multiple linear regression assisted by IBM SPSS Statistics Version 25. The results of this study demonstrate that Online Customer Review has a significant partial effect on Online Purchase Decisions of products on the Shopee marketplace by customers in Banjarmasin City. Online Customer Rating also has a significant partial effect on Online Purchase Decisions of products on the Shopee marketplace by customers in Banjarmasin City. Furthermore, both Online Customer Review and Online Customer Rating have a significant simultaneous effect on Online Purchase Decisions of products on the Shopee marketplace by customers in Banjarmasin City.